1981
DOI: 10.1149/1.2127529
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfidation Kinetics of Nickel‐Aluminum Alloys at 700°C in Hydrogen Sulfide‐Hydrogen Atmospheres

Abstract: The sulfidation kinetics of Ni‐Al alloys containing 3–13 atomic percent Al were investigated at 700°C in H2S‐H2 atmospheres at sulfur pressures 10−8 ≤PS2≤10−2 normalatm . The reaction product was comprised of three regions: an external normalNiS or Ni3S2 layer, an Al2S3‐Ni3S2 lamellar layer, and an innermost Al‐Ni‐S liquid layer. Sigmoidal shaped reaction curves before onset of linear kinetics resulted from the temporally partial protective nature of the oxide films on the metallographically polished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In .such environments sulfidation is often the predominant mode of corrosion attack. There are, however, only few investigations dealing with the high temperature corrosion of nickel aluminides in sulfidizing or mixed atmospheres [6][7][8][9]. Godlewska et al [6] investigated the sulfidation of pseudobinary p-NiAl-a-Cr alloys in sulfur vapor a t 900 and 1000°C.…”
Section: Introductionmentioning
confidence: 99%
“…In .such environments sulfidation is often the predominant mode of corrosion attack. There are, however, only few investigations dealing with the high temperature corrosion of nickel aluminides in sulfidizing or mixed atmospheres [6][7][8][9]. Godlewska et al [6] investigated the sulfidation of pseudobinary p-NiAl-a-Cr alloys in sulfur vapor a t 900 and 1000°C.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of alloys, the thermogravimetric sulfidation assembly, and phase identification techniques are described in previous papers (4,5). Typical features of scales and internal sulfidation zones resuiting from sulfidation of -y-phase Ni-A1 alloys con- decreased with increasing aluminum alloy content.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Furthermore, AGv(D is a function of supersaturation (as B --as E) and for small supersaturations AGv(oo) = w'(as B --as E) [4] Upon substitution of Eq. [4] into Eq. [3] 1…”
Section: B 4'~-~x~ Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapp and his group [13][14] carried out extensive studies pertaining to hot corrosion fluxing mechanisms, different oxide solubilities and electrochemical evaluation methods for hot corrosion resistance. Kinetic studies of various materials at high temperatures under hot corrosion conditions were reported by the earlier workers [15][16]. Natesan et al [17][18] have studied the high temperature corrosion of Ni-based superalloys in coal conversion environments.…”
Section: Propagation Stagementioning
confidence: 99%